KONTEKSTUALISASI FILSAFAT ILMU MURTADHA MUNTHAHHARI DALAM MEMBIDIK EPISTEMOLOGI UIN AR-RANIRY ACEH - Zulfata zulfata (Universitas Islam Negeri Ar-Raniry, 2016)
Murthada Munthahhari is an Iranian Muslim scholar. Many scientific disciplines are known and proven in his works and his students' researches scattered around the globe. The value of intelligence (philosophy of science) from Murtada Munthahari is important to be contextualized in the current development of science. Contextualization efforts can be linked with the development of science at Ar-Raniry State Islamic University (UIN Ar-Raniry) Aceh in forming relevant epistemological ground with related to the vision and mission of UIN Ar-Raniry Aceh. The urgency of such epistemological ground is vital as a tool of analysis in determining the progress and regression indicators of knowledge development at UIN Ar-Raniry Aceh. This article will be studied by using the theory of philosophical realism from Murthada Munthahhari, combined with the critical approach of library research. The results of this study explain that the contextualization of Murthada Munthahhari's knowledge philosophy is very relevant with the vision and mission of UIN Ar-Raniry.